2014
DOI: 10.1103/physrevb.90.020402
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and tailoring the Dzyaloshinskii-Moriya interaction in perpendicularly magnetized thin films

Abstract: We investigate the Dzyaloshinskii-Moriya interactions (DMIs) in perpendicularly magnetized thin films of Pt/Co/Pt and Pt/Co/Ir/Pt. To study the effective DMI, arising at either side of the ferromagnet, we use a fielddriven domain wall creep-based method. The use of only magnetic field removes the possibility of mixing with current-related effects such as spin Hall effect or Rashba field, as well as the complexity arising from lithographic patterning. Inserting an ultrathin layer of Ir at the top Co/Pt interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
426
5
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 412 publications
(465 citation statements)
references
References 43 publications
(50 reference statements)
31
426
5
3
Order By: Relevance
“…The inverse Co thickness dependence of the effective demagnetization field for both Cu and Ir overlayered film series is shown in Fig 2(a). For structures with the same Co thickness but different overlayers, 4πM eff has the same value, which demonstrates that Cu and Ir overlayers do not significantly influence the anisotropy field, as found previously for Pt=Co=Ir [19]. It is clear that the data in Fig.…”
Section: Fig 1 (Color Online)supporting
confidence: 70%
“…The inverse Co thickness dependence of the effective demagnetization field for both Cu and Ir overlayered film series is shown in Fig 2(a). For structures with the same Co thickness but different overlayers, 4πM eff has the same value, which demonstrates that Cu and Ir overlayers do not significantly influence the anisotropy field, as found previously for Pt=Co=Ir [19]. It is clear that the data in Fig.…”
Section: Fig 1 (Color Online)supporting
confidence: 70%
“…This is direct evidence for B diffusion from CoFeB to the adjacent layers, thus affecting in particular Ta\CoFeB interface where B segregation is expected [30]. Since the DMI is expected to be a function of the structure and in particular the atomic arrangement at the interface [21,25,26], the B accumulation at the Ta\CoFeB interface can play a major role in the generation of the positive DMI, in particular given that this presence of B is the key difference compared to CoFe-based material stacks which exhibit negative DMI. The idea that a strong accumulation of B in the bottom Ta-layer could be responsible for the character of the DMI is supported by previous works where it was reported that an N-doped Ta bottom layer can change the DMI sign compared to the case of pure Ta\CoFeB system [25].…”
Section: Boron Diffusion and Segregationmentioning
confidence: 99%
“…The driving force for the DW dynamics is the pure spin-current induced by the SHE generated in the heavy metal during the pulse injection. Furthermore, the DMI at the interface between the heavy metal and the ferromagnetic layer is responsible for the initial magnetic configuration and in particular the chirality of the DW [22,26], governing the direction of motion. As a consequence, the direction of the DWM depends on both the sign of the SHA and the sign of the DMI, where the latter fixes the chirality (left-or right-handed) of the Néel-component of the DW.…”
Section: Chiral Domain Wallsmentioning
confidence: 99%
“…An example of the latter is an interface between a magnetic metallic system and a nonmagnetic metal with strong spin-orbit coupling. For ferromagnetic systems, tunable interface-induced DM couplings have indeed been demonstrated [30][31][32][33][34][35][36]. Such interfaces typically also give rise to perpendicular anisotropies, which we therefore also take into account.…”
mentioning
confidence: 99%